The Ruling on a Judge’s Reliance on a Dog in Judicial Decisions - Mudhar Abed Abbas, (Islamic Sciences Journal, 2025)
The dog is one of God’s creatures, containing many divine wisdoms, remarkable secrets, and various benefits. This is evident in its use for guarding, hunting, and other purposes — particularly in modern times, where state authorities rely on dogs to detect explosives, combat drug trafficking, pursue criminals, and provide evidence against offenders. Accordingly, this research, following the introduction, is divided into two sections: The first section discusses the dog according to zoologists and the works written about it, and it includes two subsections. The second section explores the legal ruling on a judge’s reliance on a dog in judicial proceedings, and it consists of three subsections. Finally, the research concludes with a summary of the main findings and conclusions drawn throughout the study. .